“SI PETRUK: SISTEM INFORMASI PENDAMPINGAN TERAPI TUBERKULOSIS” SEBAGAI INOVASI PENDUKUNG PENGOBATAN PASIEN TUBERKULOSIS - Widada, Subrata Tri; Siti Nuryani; Rita Rena Pudyastuti (Bajang Institute, 2024)
Tuberculosis (TB) is a chronic disease caused by the bacterium Mycobacterium tuberculosis. In this case, tuberculosis is caused by a bacterial infection that attacks the respiratory tract of the lungs. Treatment of TB can be time-consuming and complex, as patients must undergo appropriate and disciplined drug therapy. Tuberculosis can be cured with treatment for six months to a year. In addition, TB patients also need good support and assistance in undergoing treatment. In the context of innovations supporting the treatment of TB patients, an information system called